Late-Onset Startle Syndrome and Obsessive Compulsive Disorder - Alejandro Gonzalez; Michael P. Philpot (Behavioural Neurology)
A case of late onset sporadic startle syndrome in a patient with a right posterior fossa brain tumour is reported. The exaggerated startle response did not respond to treatment with clonazepam. In addition to anxiety and depression, the patient developed obsessive- compulsive symptoms which responded to behavioural therapy. The possible mechanisms for this unique pattern of symptoms are discussed.